Effect of phenylalanine and phenylpropanoids on the accumulation of capsaicinoids and lignin in cell cultures of chili pepper (capsicum annuum L.) - Nuñez-Palenius, H.G.; Ochoa-Alejo, N.
Chili pepper (Capsicum annuum L., cv. Tampiquen~o 74)cell suspensions were employed to study the influence of phenylalanine and phenylpropanoids on the total production of capsaicinoids, the hot taste compounds of chili pepper fruits. The effect of capsaicinoid precursors and intermediates on the accumulation of lignin as an indicator of metabolic diversion was also investigated. Addition of 100mM of either phenylalanine, cinnamic or caffeic acids to chili pepper cell cultures did not cause significant increases in total capsaicinoids (expressed as capsaicin content, and calculated as averages of the measured values)during the growth cycle. The highest total capsaicinoid content was recorded in cultures grown in the presence of vanillin (142.61 mg g21 f.wt.), followed by cells treated with 100mM vanillylamine (104.88mg g21 f.wt.), p-coumaric acid (72.36 mg g21 f.wt.), and ferulic acid (34.67 mg g21 f.wt.). Capsaicinoid content for control cells was 13.97mg g21 f.wt. Chili pepper cell suspensions cultured in the presence of 100mM of either phenylalanine, or cinnamic, caffeic, or ferulic acids, or the same concentration of vanillin and vanillylamine, did not exhibit statistically significant differences in the content of lignin as compared with control cells. However, addition of p-coumaric acid (100 mM)to the culture medium significantly increased the lignin production (c. 10-15 times the contents of control cells).
Keywords: CAPSAICIN; CELL SUSPENSION; VANILLIN; VANILLYLAMINE; PHENOLICS